Composition and clumping of seeds deposited by frugivorous birds varies between forest microsites - Blendinger, Pedro Gerardo (2011)
More frequent deposition of seeds by frugivores beneath plants in fruit could impose spatial limits to the distribution of plants dispersed by animals and contribute to species coexistence. Also, differences in diet and use of microhabitats by seed dispersers could promote spatial variation in the combination of seed species deposited. We investigated patterns of seed deposition of Miconia fosteri and Miconia serrulata (Melastomataceae) by birds in the Amazon. The goal was to determine how distribution and abundance of fruiting plants, both con- and hetero-specifics, affect the spatial variability in clumping and composition of multi-specific seed deposition. We established two 9-ha plots in undisturbed terra-firme understory in the Ecuadorian Amazon. Seed rain was sampled with seed traps located in four microsites: below plants of the focal species, below Anthurium eminens (Araceae), and in randomly selected microsites. We examined seed deposition in these microsites in relation to habitat, fruiting neighborhood (fruit abundance, and distance to and density of plants of the target species), and crop size of M. fosteri or M. serrulata to determine if microsites differed in abundance and species composition of seeds. Seed traps below plants in fruit received more seeds than did randomly located traps. Seeds of the target species were, moreover, more commonly deposited below con- rather than hetero-specific plants. Seed aggregation below fruiting plants increased in forest neighborhoods where the abundance of fruits and the combination of fruiting plant species contributed to the arrival of seeds. Microsites differed notably in the combination of seeds deposited by frugivores, and differences were less pronounced among microsites that received seeds of M. fosteri and M. serrulata than among all microsites where at least some seed species were deposited by birds. We demonstrate that two closely related, ecologically similar species possess many similarities in their patterns of seed deposition and in the factors that affect those patterns. The combination of seed species deposited below foci of dispersal depended on the fruiting plant species, and the spatial patterns of seed deposition varied with the location of the microsite and the combination of co-dispersed species in the neighborhood. Similar species that share the same dispersers were confronted with different combinations of seeds depending on the microsite where they arrived, which could promote forest heterogeneity in the combination of plant species.